Pengaruh Budaya Organisasi dan Kepemimpinan Terhadap Kinerja Karyawan dengan Komitmen Organisasi Sebagai Variabel Intervening pada Kantor KUD Sinar Makmur - Anisa Oktana Bela; Yosi Yulia; Ramdhani Bayu Putra; Hasmaynelis Fitri (Yayasan Kawanad, 2022)
This study aims to determine how big the influence of organizational culture and leadership on employee performance with organizational commitment as an intervening variable at the KUD Sinar Makmur Dharmasraya Office. The research variables are Organizational Culture (X1), Leadership (X2), Employee Performance (Y), and Organizational Commitment (Z). The method of collecting data is through surveys and distributing questionnaires to employees as respondents. The analytical method used is the test of the outer model and the inner model using the SmartPLS 3.0 data processing tool. The results show (a) Organizational Culture has a positive and significant effect on Organizational Commitment of 7.771 with a significant level (0.000 <0.05) (b) Leadership has a positive and insignificant effect on Organizational Commitment of 1.672 with a significant level (0.067>0.05) (c) Organizational Culture has a positive and significant effect on Employee Performance of 2,321 with a significant level (0.027 <0.05) (d) Leadership has a positive and significant effect on Employee Performance, of 12,993 with a significant level (0.000 <0.05) (e) Organizational Commitment has a positive effect and not significant to Employee Performance of 2,095 with a significant level (0.049 <0.05) (f) Organizational Culture has a positive and insignificant effect on Employee Performance through Organizational Commitment of 1.883 with a significant level (0.070> 0.05) (g) Leadership positive and insignificant effect on Employee Performance Through Organizational Commitment r 1.486 with a significant level (0.162>0.05). Based on the results of this study, it is expected that KUD Sinar Makmur Dharmasraya employees can improve their performance by improving leadership, and increasing organizational commitment.